Silver-hollow mesoporous silica nanoparticles for clarithromycin delivery in an animal model of helicobacter pylori - Soroush Mirfakhraee; Reza Mirnejad; Maryam Iman (Nanomedicine Journal)
Background: Nanoparticle-based drug delivery systems offer a promising approach to overcoming antimicrobial resistance and enhancing therapeutic efficacy.Objective(s): This study aimed to evaluate the efficacy of silver-hollow mesoporous silica nanoparticles (Ag-HMSNs) in the targeted delivery of clarithromycin for eradicating Helicobacter pylori (H. pylori).Materials and Methods: A synergistic formulation comprising silver nanoparticles and clarithromycin-loaded hollow mesoporous silica nanoparticles (Ag-HMSNs@CLT) was examined for its antibacterial activity against H. pylori.  The effectiveness of various anti-H. pylori formulations was determined using in vitro inhibition assays and in vivo bacterial load reduction studies.Results: The hollow mesoporous silica nanoparticles (HMSNs) demonstrated a high drug-loading capacity, with a clarithromycin content of 27%. The minimum inhibitory concentrations (MIC) for silver nanoparticles (Ag NPs), clarithromycin (CLT), and Ag-HMSNs@CLT were <2 μg/mL, <0.5 μg/mL, and <0.25 μg/mL, respectively. Among the tested formulations, Ag-HMSNs@CLT exhibited the most pronounced reduction in bacterial load during in vivo studies and significantly mitigated inflammation, as evidenced by hematoxylin-eosin staining.Conclusion: The developed nanoparticle-based drug delivery system exhibited excellent drug-loading efficiency and controlled drug release over an extended period. This study highlighted the potential synergistic effects of combining anti-H. pylori agents and their efficacy in reducing bacterial growth and alleviating gastrointestinal complications associated with H. pylori infection.